Boundary Layer Flow, Heat And Mass Transfer Of Cu-water Nanofluid Over A Moving Plate With Soret And Dufour Effects: Stability Analysis - Najwa Najib; Norfifah Bachok (Akademia Baru Publishing (M) Sdn Bhd, 2024)
Indexed by MyCite